People-related total quality management practices, job satisfaction and turnover intention in electrical and electronics industry in Malaysia - Yue, Jing Wen (2019)
Electrical and Electronics (E&E) industry in Malaysia is currently facing high employee turnover. Employee turnover is part of human capital risk that could bring detrimental effects to organisations if it is not managed effectively. Arising from this concern, this research is motivated to analyse whether people-related Total Quality Management (TQM) practices can enhance employee satisfaction and lower turnover intention among the employees. This study aims to assess the multidimensional and mediating relationships between turnover intention, job satisfaction, and six peoplerelated TQM practices, namely, teamwork, employee involvement, reward and recognition, employee empowerment, training and development, and leadership. After conducting an extensive literature review, nineteen hypotheses are constructed and tested using quantitative cross-sectional research based on 244 valid responses from the employees of ISO-certified E&E companies in Malaysia. The survey findings are analysed using the “Partial Least Square approach to Structural Equation Modeling” via SmartPLS version 3.0. Results from the analysis indicate that leadership, reward and recognition, teamwork, and empowerment lead to enhanced job satisfaction. In addition, leadership, training and development, and empowerment reduce turnover intention. Job satisfaction is found to mediate the links between reward and recognition, teamwork, leadership, empowerment and turnover intention. A major theoretical contribution of this study is the validation of the people-related TQM practices–attitude–behaviour relationship based on Social Exchange Theory and Job Embeddedness Theory. Practically, this study has developed recommendations and a Strategic Human Capital Risk Management Framework for the industry practitioners and policymakers to manage human capital risks effectively. It is also important for organisations to balance hard TQM practices with people-related TQM practices and place justifiable focus on employee satisfaction. Recognising the importance of E&E industry, policymakers should collaborate with industry players to produce and retain quality human capital in order to attain sustainable competitive advantage for E&E industry and the nation.